Analysis of High School Students' Preconceptions on the Concept of Climate Change from the Perspective - Darmawan, Deni; Hardiani, Santi; Mulyani, Agustina; Nugraha, Wildan; Wasiat, Raji (Devotion : Journal of Research and Community Service, 2024)
Preconception is a very important initial understanding for students to have, because preconception can be used as a basis for better learning. One of them is regarding the concept of climate change material, there are still many students who have wrong conceptions. One way to find out students' preconceptions is by using visual representations. The use of visual representation can open students' preconceptions of abstract and complex concepts. This study aims to see and analyze the extent of high school students' understanding of climate change. This study uses qualitative descriptive, with a population and sample consisting of 63 tenth-grade high school students majoring in science at one of the high schools in Indonesia. The data collection technique was carried out by observation and interviews, in this study the researcher used semi-structured interviews. The results of the study revealed that students have a varied understanding of the concept of climate change, there are still many students who experience misconceptions about the concept of climate change. There are three categories of climate change concepts (1) the concept of climate change is correct with a percentage of 37% (23 students), 2) the concept of climate change is based on objects, reviewed from the overall picture that has been visualized by the respondents and 3) the concept of climate change is wrong with a proportion of 63% (40 students).  Of the three categories above, based on empirical evidence that has been carried out regarding students' preconceptions of climate change, including at the macroscopic level.